Planar asymmetric surface FeIV = O synthesis with pyrite and chlorite for efficient oxygen atom transfer reactions - Lian, Wengao; Xu, Hengyue; Zou, Xingyue; Dai, Jie; Li, Meiqi; Ling, Cancan; Shen, Yunhao; Li, Hao; Yao, Yancai; Zhang, Lizhi (Nature communications, 2025)
Surface high-valent iron-oxo species (≡Fe IV =O) are reliable and green oxygen atom transfer reagents, but the ability is seriously inhibited by the maximal orbital overlap of axial Fe = O double bond in a symmetric planar coordination environment. Herein, we report the synthesis of planar asymmetric surface Fe IV = O (PA-≡Fe IV = O) on pyrite using chlorite as the oxidant, where the in-situ generated ClO 2 can transform a planar Fe-S bond to Fe-Cl by oxidizing and subsequently substituting planar sulfur atoms. Different from planar symmetric surface Fe IV = O (PS-≡Fe IV = O) with electron localization around axial Fe = O, PA-≡Fe IV = O delocalizes electrons among Fe, axial oxo moiety and its planar ligands owing to the stronger electron-withdrawing capacity of Cl, which effectively weakens the orbital overlap of axial Fe = O bonding and thus facilitates the rapid electron transfer from the substrates to the unoccupied antibonding orbital of PA-≡Fe IV = O, realizing more efficient oxygen atom transfer oxidation of methane, methyl phenyl sulfide, triphenylphosphonate and styrene than PS-≡Fe IV = O. This study offers a facile approach for the synthesis of planar asymmetric surface Fe IV = O, and also underscores the importance of planar coordination environment of high-valent metal-oxo species in the oxygen atom transfer reactions. Surface high-valent iron-oxo species (≡Fe⁴⁺=O) are effective and environmentally friendly reagents for oxygen atom transfer. Here, the authors create a planar, asymmetric ≡Fe⁴⁺=O with a Fe–Cl₁S₃ structure using pyrite and chlorite, which enhances electron delocalization and weakens the Fe=O bond to improve reaction efficiency.